Analisis Faktor-Faktor yang Mempengaruhi Keputusan Wisatawan Berkunjung ke Bali Zoo di Singapadu, Gianyar - I Gede Surya Pratama; I Made Indra Wiraguna (Warmadewa Management and Business Journal (WMBJ), 2019)
The study "Analysis of Factors Affecting Tourist Decisions to Visit Bali Zoo in Singapadu, Gianyar" raises two compulsory problems, namely the one that addresses the factors that influence the decision of tourists to visit Bali Zoo and the one that highlights the variables that represents each of the factors that influence the tourist decisions. The objectives of the study are to find out the factors that influence tourists 'decisions to visit Bali Zoo and to reveal the variables that represent each of the factors that influence the decisions of tourists. The data used in this study are quantitative data and qualitative data that were obtained from primary data and secondary data. Samples in this study were tourists who were visiting the Bali Zoo and met by the researcher. The sampling technique used was accidental sampling technique and was applied to select a total sample of 60 people. From the results of the study using factor analysis, it is obtained that there are 2 factors that influence touristsâ€™ decisions to visit Bali Zoo in Singapadu, Gianyar. These two factors explain all the variants in the data and are named according to the surrogate approach, namely the factor of cleanliness of the place consisting of variable cleanliness of the place, completeness of facilities, location, design of the place, means of transportation, courtesy of employees, reference groups and family; and the factor from the job consisting of the job variables, the employee friendliness, the price discounts, and the income. Penelitian ini berjudul â€œAnalisis Faktor-Faktor Yang Mempengaruhi Keputusan Wisatawan Berkunjung Ke Bali Zoo Di Singapadu, Gianyarâ€. Mengangkat dua perumusan masalah yaitu faktor-faktor apa saja yang mempengaruhi keputusan wisatawan berkunjung ke Bali Zoo dan variabel apa saja yang mewakili setiap faktor yang mempengaruhi keputusan wisatawan berkunjung ke Bali Zoo di Singapadu, Gianyar. Tujuan penelitian, yaitu untuk mengetahui faktor-faktor yang mempengaruhi keputusan wisatawan berkunjung ke Bali Zoo dan untuk mengetahui variabel yang mewakili setiap faktor-faktor yang mempengaruhi keputusan wisatawan berkunjung ke Bali Zoo. menggunakan data kuantitatif dan data kualitataif dimana sumber data yang dipergunakan adalah data primer dan data sekunder.Sampel dalam penelitian ini adalah wisatawan yang telah berkunjung yang secara kebetulan bertemu dengan peneliti di Bali Zoo. Pengambilan sampel dilakukan dengan teknik accidental sampling dengan jumlah sampel sebanyak 60 orang. Didapat hasil penelitian dengan menggunakan analisis faktor, 2 faktor yang mempengaruhi wisatawan berkunjung ke Bali Zoo di Singapadu, Gianyar. Faktor tersebut menjelaskan semua varian yang ada di dalam data, kedua faktor tersebut diberi nama sesuai dengan pendekatan surrogate yaitu Faktor kebersihan tempat terdiri dari variabel kebersihan tempat, kelengkapan fasilitas, lokasi, desain tempat, sarana transportasi, kesopanan karyawan, kelompok referensi serta keluarga dan faktor pekerjaan terdiri dari variabel pekerjaan, keramahan karyawan, potongan harga serta pendapatan.